Energy Dispersive X-ray Fluorescence Analysis of Pre and Post-1850 Historical Documents Obtained from the National Library of South Africa - Dzinavatonga, K.; Medupe, T.R.; Prinsloo, L.C.; E. Ebenso, Eno (Asian Journal of Chemistry, 2013)
Energy dispersive X-ray fluorescence technique was used to study the elemental composition of some historical paper samples obtained from the National Library of South Africa. Six elements namely Fe, Cu, Mn, Ca, K and S were detected. It was found that older documents had higher concentrations of Ca and hence a considerable alkaline buffer than recent documents. It was also observed that the levels of Ca dropped significantly between 1800 and 1890 coinciding with the period paper making technology also changed. The concentrations of K and S also decreased around 1890. Iron remained fairly high and was detected in all the samples. Copper and manganese were found to be at very low concentrations compared to Fe. This research shows that Fe has the potential to impact negatively on paper permanency unless de-acidification is undertaken because of its relative abundance compared to Cu.